Urachal Adenocarcinoma: A Case Report of Rare Tumor in Women - Setya, Rindha Ilyasa; Prasetyawan, Widiyanto (Brawijaya Journal of Urology, 2026)
Introduction. Urachal adenocarcinoma is an uncommon malignancy that typically presents in older men, and its recognition is often delayed because early symptoms are vague. This report is distinctive because it involves a young female patient with a mucinous colon-type immunophenotype, a presentation that is unusually atypical for urachal tumors and can easily be mistaken for a gastrointestinal primary. This rare combination of demographic and pathological features makes the case clinically significant, as it highlights specific diagnostic pitfalls that are not commonly emphasized in the literature. Case. A 40-year-old woman experienced recurrent dysuria and visible hematuria for one year. CT imaging revealed a mass at the bladder dome extending toward the umbilicus, raising suspicion for a urachal lesion. Following cystoscopic biopsy suggesting mucinous adenocarcinoma, the patient underwent surgical extirpation with partial cystectomy. Histopathology accompanied by immunohistochemistry demonstrated CK7 negativity with CK20, CDX2, and β-catenin positivity, an immunoprofile characteristic of colon-type urachal adenocarcinoma. Conclusion. Early cross-sectional imaging for persistent hematuria, close attention to masses located at the midline bladder dome, and the routine use of immunohistochemical markers to differentiate urachal from colorectal adenocarcinoma are essential steps to enhance diagnostic accuracy. Incorporating these strategies may prevent missed or delayed diagnoses in similarly atypical presentations of urachal adenocarcinoma.